The Poetics of Expiration: Felicia Hemans - Robinson, Jeffrey (Romanticism on the Net, 2003)
AbstractHemans’s “poetics of expiration” is contrasted to the high Romantic “poetics of effusion,” the former devoted to insubstantiality, the latter to the monumental. Critics from Walter Scott to Kingsley Amis have berated Hemans’s extreme superficiality, but, as Jerome McGann has argued, it can be seen as her bid to imagine substance on the brink of its dissolution. This essay shows, through careful readings of her poems, that though dissolution and death figure in this poetics of expiration, at its heart is a reversal from “emptying out” to “proliferation.” A dying into the moment has a certain life-yield that Hemans calls “holiness.” Reading not only the reception history of Hemans but also Hemans’s reception of high Romantic poets show us that we have misunderstood her aims: attuning ourselves to her praise for the enactment of her highest poetic goals in poetry by others helps us to see them in her works as well.